Dulaan a documentary on the Spanish influence on Philippine theater - Tiongson, Nicanor G.; Del Mundo, Jaime; Marasigan, Dennis N. (Tuklas sining series, 1992)
This video discusses the various forms of Spanish-influenced theater - from the komedya, the sinakulo, the sarswela to the drama - and how contemporary playwrights and theater groups have revived or innovated them.